The Effect of Leadership Style and Competence on EmployeePerformance at UPTD BBIS Aikmel - Amira Diva (Journal of Accounting, Management, and Economic Development, 2025)
Leadership style is the pattern of behavior of a leader in influencing his followers. Competence is the basic characteristic of a person (individual) that influences the way he thinks and acts. Performance is the result of work in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with his responsibilities. This study aims to analyze the influence of leadership style and competence on the performance of employees at UPTD BBIS Aikmel. This study uses a quantitative approach with data collection techniques through direct interviews and the distribution of online questionnaires to 30 respondents who are employees of UPTD BBIS Aikmel. The data was analyzed using Structural Equation Modeling with Partial Least Square (PLS). The results of this study indicate that employee performance at UPTD BBIS Aikmel is significantly influenced by leadership style and competence. These findings can serve as a reference and provide insights for future similar research in decision-making.